Pembuatan Alat Pengolahan Air Sederhana Untuk Kebutuhan Air Bersih Di Kampung Pamaris Desa Gunungtua Kecamatan Cijambe Kabupaten Subang - Sugeng Sutikno; Deny Ernawan; Yusup Yulianto; Yudha Ramadhan; Andris Ramdani (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2022)
Pamaris Village is located in the highlands of Gunungtua Village, Cijambe District, Subang Regency. The existence of this area which is located in the highlands makes it difficult for the community to get clean water for their daily needs. Has a river flow that is used for agricultural and fishery water but is not utilized for clean water needs because the community doubts the quality of river water to be used as a source of clean water. With the background of the problems in Pamaris village, the lecturers and students of the Civil Engineering study program, Faculty of Engineering, University of Subang took the initiative to do community service by making a simple water treatment tool to treat river water so that it can be used to meet the community's clean water needs. The planned water treatment system consists of a coagulation tank, a sedimentation tank, a slow sand filter and a fast sand filter. The filter material consists of coral, palm fiber, zeolite, split stone, palm fiber, activated carbon and sand. The results of testing the treated water showed that all parameters of Physics, Inorganic Chemistry and Organic Chemistry were still within the limits of clean water quality standards. The results of bacteriological examination did not find bacteria. Thus, in general, water quality can be used as a source of clean water for the community.